Big Data as An Emerging Paradigm in Organisations’ Management: A Bibliometric Analysis - Gonçalves, Sidalina; Ventura, José Biléu; Rua, Orlando Lima; Dias, Rui; Galvão, Rosa (Journal of Ecohumanism, 2024)
The Big Data Age defines the present era, and the globalisation of business makes it pressing to derive valuable insights from data so that organisations can make sustained decisions. There is no consensus in the literature on how organisations should guide the vast volume of data in value creation or galvanise performance gains. The study aims to address these gaps by reviewing the literature searching WoS using R. Bibliometrix. 4,019 documents were identified between 2008 and early February 2022 through a current mapping of Big Data in management. The results indicate a strong collaboration network among authors and a notable trend in Big Data, Big Data Analytics, Machine Learning, and Artificial Intelligence. These keywords reveal a concern for the predictive analysis of data and the emergence of new research trends, namely management, performance, decision-making, business and value creation, supporting the thesis that Big Data is an emerging paradigm in organisational management.